2017
DOI: 10.1007/s11274-017-2205-x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen fixing bacterial diversity in a tropical estuarine sediments

Abstract: Microorganisms play a significant role in biogeochemical cycles, especially in the benthic and pelagic ecosystems. Role of environmental parameters in regulating the diversity, distribution and physiology of these microorganisms in tropical marine environment is not well understood. In this study, we have identified dinitrogen (N) fixing bacterial communities in the sediments by constructing clone libraries of nitrogenase (nifH) gene from four different stations in the Cochin estuary, along the southeastern Ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…The CE is highly disturbed with various anthropogenic activities by many industries and sewage inputs , this may also influence nearby coastal waters. However, the recent reports in the CE by Thajudeen et al in sediments and Bhavya et al in the water column reveals that CE is the region of the active nitrogen fixation process.The nitrogen fixation rate in sediments of CE was observed to be between 0.25 and 0.74 nmol Ng −1 h −1 , while that of water column was found to be 0.59–1.3 nmol Nl −1 h −1 .…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The CE is highly disturbed with various anthropogenic activities by many industries and sewage inputs , this may also influence nearby coastal waters. However, the recent reports in the CE by Thajudeen et al in sediments and Bhavya et al in the water column reveals that CE is the region of the active nitrogen fixation process.The nitrogen fixation rate in sediments of CE was observed to be between 0.25 and 0.74 nmol Ng −1 h −1 , while that of water column was found to be 0.59–1.3 nmol Nl −1 h −1 .…”
Section: Discussionmentioning
confidence: 90%
“…Amplification with nifH gene primer yielded about 360‐bp size product on agarose gel. Our previous study on nifH gene based metagenome approach, also pointed out that nutrient rich surface sediment environment of CE has good diversity of heterotrophic bacteria and these heterotrophs might play an influential role in regulating estuarine nitrogen budget. Our study revealed the presence of nifH gene in B. megaterium , B. cereus , B. safencis , B. licheniformis , B. aerophilus , B. oceanisediminis , and B. flexus (isolates from estuary) and B. subtilis , B. megaterium , B. circulans , B. aerophilus , B. flexus , and B. Oceanisediminis (isolates from coastal environments).…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies in marshes of the southeastern US show that plant photosynthetic activity and rhizodeposition stimulate N fixation by root-associated sulfate reducers (Whiting et al, 1986; Gandy and Yoch, 1988; Lovell et al, 2000). Consistently, prokaryotic species from the Desulfobulbus, Desulfatitalea , Desulfovibrio, and Sulfurospirillum genera, either significantly enriched or members of the S. alterniflora root core microbiome, have been shown to couple sulfate or sulfur respiration to N fixation (Higashioka et al, 2015; Thajudeen et al, 2017). Species from the root and rhizosphere core microbiome genera Candidatus Thiodiazotropha and Thioalkalispira have the metabolic potential to couple S oxidation with C and N fixation (Barbieri et al, 2010; Petersen et al, 2016).…”
Section: Discussionmentioning
confidence: 94%
“…Sulfur oxidation may be mediated not only by Candidatus Thiodiazotropha bacteria, but also members of the Sulfurovum and Thioalkalispira genera, or endosymbionts from the Thiomicrospirales order. Previously studied microbial species from the Sulfurovum genus and endosymbionts from the Thiomicrospirales order have been demonstrated to fix C; whereas members from Desulfovibrio , Thioalkalispira , and Candidatus Thiodiazotropha genera have been shown to perform both C and N fixation (Barbieri et al, 2010; Petersen et al, 2016; Suzuki et al, 2006; Thajudeen et al, 2017). Moreover, Crump et al (2018) studying the root microbiome of seagrass Zostera spp., found high transcripts levels of N fixing and sulfur oxidizing genes from Gammaproteobacteria species, including endosymbionts of marine invertebrate from the Sedimenticolaceae family, which includes the Candidatus Thiodiazotropha genus.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies, targeting the microbes actively expressing the genetic machinery for N fixation in Narragansett Bay sediments in 2006 and subsequent years, revealed that the major contributors to this process were 2 groups of anaerobes belonging to Desulfovibrionaceae and Geobacteraceae (Fulweiler et al 2013, Brown & Jenkins 2014. Anaerobic bacteria have also been identified as important N fixers in other estuarine systems (Bertics et al 2013, Bentzon-Tilia et al 2015, Fan et al 2015, Newell et al 2016, Thajudeen et al 2017.…”
Section: Introductionmentioning
confidence: 99%